2013
DOI: 10.1128/aac.00730-13
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Efflux Pumps, Porins, and β-Lactamases to Multidrug Resistance in Clinical Isolates of Acinetobacter baumannii

Abstract: eWe investigated the mechanisms of resistance to carbapenems, aminoglycosides, glycylcyclines, tetracyclines, and quinolones in 90 multiresistant clinical strains of Acinetobacter baumannii isolated from two genetically unrelated A. baumannii clones: clone PFGE-ROC-1 (53 strains producing the OXA-58 ␤-lactamase enzyme and 18 strains with the OXA-24 ␤-lactamase) and clone PFGE-HUI-1 (19 strains susceptible to carbapenems). We used real-time reverse transcriptase PCR to correlate antimicrobial resistance (MICs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
150
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 48 publications
16
150
1
Order By: Relevance
“…Resistance to quinolones is developed through different methods, one of which is the changes occurred in the expression of the efflux pumps. The efflux pump in A. baumannii is the AdeABC pump and is of great importance in terms of resistance creation (10). One of the mechanisms to deal with the antibiotic resistance is to block or disrupt the mechanisms leading to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to quinolones is developed through different methods, one of which is the changes occurred in the expression of the efflux pumps. The efflux pump in A. baumannii is the AdeABC pump and is of great importance in terms of resistance creation (10). One of the mechanisms to deal with the antibiotic resistance is to block or disrupt the mechanisms leading to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the efflux pumps, the organism has been shown to harbor representatives of each of the five so-called bacterial drug efflux pump families: CraA and AmvA are major facilitator superfamily (MFS) pumps that are proposed to efflux chloramphenicol and erythromycin, respectively (13,14), AbeM is a multidrug and toxic compound extrusion (MATE) family protein that effluxes aminoglycosides, quinolones, and chloramphenicol (15), AbeS is a small multidrug resistance (SMR) family pump that confers resistance to erythromycin and novobiocin, as well as low-level tolerance to aminoglycosides, quinolones, tetracycline, and trimethoprim (16), AdeABC, AdeFGH, and AdeIJK are resistance-nodulation-division (RND) family pumps that have been associated with resistance to aminoglycosides, ␤-lactams, fluoroquinolones, tetracyclines, tigecycline, macrolides, chloramphenicol, and trimethoprim (17)(18)(19)(20)(21). Furthermore, A. baumannii is known to harbor several horizontally acquired Tet efflux pumps belonging to the MFS that confer tetracycline resistance (12,22). While the antimicrobial effects of these efflux pumps have been well documented, the mechanisms by which the organism regulates their expression are only beginning to be understood.…”
mentioning
confidence: 99%
“…baumannii antibiotic resistance is thought to be mediated by an expansive repertoire of enzymatic determinants, such as ␤-lactamases, as well as efflux pumps that extrude toxic agents, including antibiotics, from the cell (3,11,12). With regard to the efflux pumps, the organism has been shown to harbor representatives of each of the five so-called bacterial drug efflux pump families: CraA and AmvA are major facilitator superfamily (MFS) pumps that are proposed to efflux chloramphenicol and erythromycin, respectively (13,14), AbeM is a multidrug and toxic compound extrusion (MATE) family protein that effluxes aminoglycosides, quinolones, and chloramphenicol (15), AbeS is a small multidrug resistance (SMR) family pump that confers resistance to erythromycin and novobiocin, as well as low-level tolerance to aminoglycosides, quinolones, tetracycline, and trimethoprim (16), AdeABC, AdeFGH, and AdeIJK are resistance-nodulation-division (RND) family pumps that have been associated with resistance to aminoglycosides, ␤-lactams, fluoroquinolones, tetracyclines, tigecycline, macrolides, chloramphenicol, and trimethoprim (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The AdeABC pump is present in approximately 80% (53% to 97%) of A. baumannii clinical strains [2,14]. Our study showed the presence of the adeB gene in all 120 A. baumannii clinical isolates.…”
Section: Discussionmentioning
confidence: 68%